End of Life Care: What is Important for Me and for Us. A Review of Recent UK Strategy and Policy Documents and their Implications for Chaplains. (11th February 2017) - Matthews, Pia
Abstract : This article reviews some recent UK strategy and policy documents about building a "national choice offer" to enable end of life care to be delivered at home, and encouraging the formation of supportive communities. Notably, with the implicit assumption that planned choice is sufficient for end of life care, the contribution of healthcare chaplaincy is neglected. The article explores the implications for healthcare chaplains, how chaplains can help to build up compassionate communities, and some practical aspects of community support for those of faith and no faith through initiatives for parish support.